2019
DOI: 10.3390/nano9050724
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a Flower-Like g-C3N4/ZnO Hierarchical Structure with Improved CH4 Sensing Properties

Abstract: In this paper, a hierarchical structure of graphite carbon nitride (g-C3N4) modified ZnO (g-C3N4/ZnO) was synthesized using a simple precipitation-calcination method. Through this method, g-C3N4 nanosheets with a controlled content were successfully decorated on the petals of flower-like ZnO. Various techniques were used to confirm the successful formation of the g-C3N4/ZnO hierarchical structure. The methane (CH4) sensing properties of g-C3N4/ZnO sensor were investigated. The result exhibited that after decor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 49 publications
3
13
0
Order By: Relevance
“…The chemiresistive sensor fabricated in this study shows excellent gas response of $8.6 (760% sensitivity) at 1000 ppb concentration of methane gas. The sensors fabricated in the present study demonstrates excellent features towards methane gas detection in low concentrations at room temperatures in comparison to recent studies [42][43][44][45][46][47][48][49][50][51][52] as summarized in Table 2. To the best of our knowledge this is the rst study reported with such a high performance for room temperature detection of greenhouse methane gas at ppb level.…”
Section: Methane Gas Sensing Performancementioning
confidence: 61%
“…The chemiresistive sensor fabricated in this study shows excellent gas response of $8.6 (760% sensitivity) at 1000 ppb concentration of methane gas. The sensors fabricated in the present study demonstrates excellent features towards methane gas detection in low concentrations at room temperatures in comparison to recent studies [42][43][44][45][46][47][48][49][50][51][52] as summarized in Table 2. To the best of our knowledge this is the rst study reported with such a high performance for room temperature detection of greenhouse methane gas at ppb level.…”
Section: Methane Gas Sensing Performancementioning
confidence: 61%
“…Over the last few years, much effort has been focused on the search of methods for enhancement of photocatalytic activity of carbon nitride. Attempts have been made to increase its specific surface area (SSA) using the hard template method [11,[16][17][18][19][20][21] and to reduce the energy specific surface area (SSA) using the hard template method [11,[16][17][18][19][20][21] and to reduce the energy gap by doping with heteroatoms [22][23][24][25][26][27][28] or exfoliation [29,30]. Although these methods have been proved as effective, they are multistage and thus expensive.…”
Section: Introductionmentioning
confidence: 99%
“…During the past few years, many research groups have reported different types of heterojunction photocatalysts comprised of g-C 3 N 4 and metal oxides or sulphides showing improved photothermal conversion efficiencies when compared with their individual components. 32,[35][36][37][38][39] Inspired by the above efforts, we herein construct a selfassembled PTT agent, PEG-CuS@g-C 3 N 4 by a rapid and simple recrystallization growth which was schematically illustrated in Scheme 1. In this composite, CuS played a role in generating hyperthermia under the NIR irradiation.…”
Section: Introductionmentioning
confidence: 99%